2019
DOI: 10.1128/jcm.00875-19
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Performance of HRP2 Antigen Detection for Malaria Diagnosis in Mozambique

Abstract: Rapid diagnostic tests (RDTs) that detect the Plasmodium falciparum-specific histidine-rich protein 2 (PfHRP2) antigen are the primary methods for malaria diagnosis in Mozambique. However, these tests do not detect infections with non-falciparum malaria or Pfhrp2- and Pfhrp3-deleted P. falciparum parasites. To assess the appropriateness of conventional PfHRP2-only RDTs for malaria diagnosis in Mozambique, samples collected during a health facility survey conducted in three provinces of Mozambique were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
(32 reference statements)
2
19
0
Order By: Relevance
“…This study revealed that the sensitivity of both RDTs increased among febrile individuals, to 84.9 for uRDTs and 79.2 for cRDTs. This indicates that febrile cases which usually suffer from higher density infections as shown in this study (GMPD of 346.3 parasites/µL), are likely to be rightly diagnosed with both types of RDTs in southern Mozambique [32]. Therefore, this suggests that uRDTs do not provide added benefits to the detection of infections among febrile individuals in the community when compared to regular RDTs, a finding that has been similarly observed among febrile outpatients in Tanzania [27].…”
Section: Discussionsupporting
confidence: 53%
“…This study revealed that the sensitivity of both RDTs increased among febrile individuals, to 84.9 for uRDTs and 79.2 for cRDTs. This indicates that febrile cases which usually suffer from higher density infections as shown in this study (GMPD of 346.3 parasites/µL), are likely to be rightly diagnosed with both types of RDTs in southern Mozambique [32]. Therefore, this suggests that uRDTs do not provide added benefits to the detection of infections among febrile individuals in the community when compared to regular RDTs, a finding that has been similarly observed among febrile outpatients in Tanzania [27].…”
Section: Discussionsupporting
confidence: 53%
“…As Uganda advances towards malaria elimination, false-negative RDT results due to low-parasite density infections will be a potential threat [61,62]. Efforts to address low-parasite density infections should consider the deployment of highly sensitive diagnostic tools, including nucleic acid amplification-based tests [61,[63][64][65][66][67][68]. However, the current WHO guidance does not recommend the use of ultrasensitive RDTs for routine diagnosis until additional evidence becomes available [67].…”
Section: Implication For Malaria Controlmentioning
confidence: 99%
“…A substantial proportion of parasite isolates with both pfhrp 2 and pfhrp 3 gene deletions have been reported across malaria endemic countries in Africa with the highest prevalence of deletion from Eritrea (62%) [ 14 ] and the lowest from Angola (0.4%) [ 19 ]. Indeed, in some hospitals in Eritrea the levels of gene deletions were as high as 80% [ 14 ].…”
Section: Introductionmentioning
confidence: 99%